Franco-German relations in the Gaullist thought - Lesiński, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The presented article attempts to describe and analise the evolution of Charles de Gaulle’s ideas regarding the relations between states and nations of France and Germany. Beginning with the first look towards the eastern neighbour, through the events of interwar period until the time of de Gaulle’s presidency, the article presents ideas and demands formulated by de Gaulle in the issue of franco-german relations. The article also describes the process of evolution of Gaullist approach, from the desire of the vengeance on Germans to the belief in the need of reconciliation of two nations. The article intends to prove that the franco-german relations (as viewed by de Gaulle), just like gaullism itself, had one pragmatic object: to ensure „the greatness of France”. The last object of the article is to disenchant the „romantic history” of franco-german post-war reconciliation. To achieve this object the article analises the views and postulates of German chancellor Konrad Adenauer the second great architect of franco-german reconciliation.

Przedstawiony artykuł podejmuje próbę opisania i analizy ewolucji koncepcji Charles’a de Gaulle’a na stosunki Francji i Niemiec oraz narodów: francuskiego i niemieckiego. Począwszy od pierwszego spojrzenia w kierunku wschodniego sąsiada, poprzez wydarzenia okresu międzywojennego, aż do czasu prezydentury de Gaulle’a przedstawione zostały założenia i postulaty, jakie formułował odnośnie do relacji francusko-niemieckich. Wykazany został również proces ewolucji, jaką przeszły koncepcje de Gaulle’a na przestrzeni lat; od chęci wzięcia rewanżu na Niemcach aż do przekonania o potrzebie pojednania narodów. Artykuł ma udowodnić również tezę, iż relacje francusko-niemieckie podobnie jak cała doktryna gaullistowska w sposób pragmatyczny miały realizować jeden cel: zapewnić Francji „wielkość”. Wykorzystane zostały również spostrzeżenia i koncepcje drugiego z architektów pojednania francusko-niemieckiego – Konrada Adenauera. Zapewni to realizację ostatniego z celów niniejszego artykułu, jakim jest swoiste „odczarowanie” romantycznej historii o francusko-niemieckim pojednaniu poprzez wskazanie pragmatycznych celów obu państw, które leżały u jego podstaw.
Keywords: Charles de Gaulle; gaullism; Germany; France; Konrad Adenauer; reconciliation; franco-german relations; gaullizm; Niemcy; Francja; pojednanie; relacje francusko-niemieckie